PUBLIC OPINION ON DIABETES MELLITUS IN CHENNAI - ANUSHA.G, Dr. Sreeya B (International Journal of Advanced Science and Technology, 2020)
This research is made to observe public opinion on diabetes mellitus. Type one Diabetes mellitus conjointly called growth-onset diabetes could be a chronic illness characterized by hormone deficiency to exocrine gland β-cell loss and ends up in hyperglycemia. Though the age of symptomatic onset is typically throughout childhood or adolescence, symptoms will typically develop abundant later. Though the aetiology of type one diabetes mellitus isn't fully understood, the pathological process of the illness is assumed to involve T cell-mediated destruction of β-cells. The objective of the study is to know the difference in the mean scores of level of agreeability towards prevention of diabetes among the education qualification of the respondents, and to analyse the difference between the opinion on biggest risk factor of diabetes and gender of the respondents. Descriptive research method and convenient sampling method is used. 1540 is the sample size. Dependent variables are Diabetes is an important consent, factors of diabetes, Get plenty of fiber, Skipping food, Physical activity, Lose extra weight. Statistics used are chi-square, Independent sample t-test, and ANOVA. Diabetes patients should go for regular check up to the hospital. Encourage clinical research in diabetes mellitus. It shows that the awareness of diabetes mellitus is required. It was found that there is association between diabetes an important consent in today's scenario and age of the respondents. It was also found that there is difference between the opinion on biggest risk factor of diabetes and gender of the respondents. Therefore it has been concluded that awareness towards diabetes should be increased among Chennai people. For better future the youngsters need to concentrate on health to avoid various problems.